Defining a New Biomarker for the Autoimmune Component of Multiple Sclerosis: Th40 cells - Waid, Dan M. (2014)
Multiple Sclerosis (MS) is a chronic inflammatory, neurodegenerative disease. Diagnosis is very difficult requiring defined symptoms and multiple CNS imaging. A complicating issue is that almost all symptoms are not disease specific for MS. Autoimmunity is evident, yet the only immune-related diagnostic tool is cerebral-spinal fluid examination for oligoclonal bands. This study addresses the impact of Th40 cells, a pathogenic effector subset of helper T cells, in MS. MS patients including relapsing/remitting MS, secondary progressive MS and primary progressive MS were examined for Th40 cell levels in peripheral blood and, similar to our findings in autoimmune type 1 diabetes, the levels were significantly (p < 0.0001) elevated compared to controls including healthy non-autoimmune subjects and another non-autoimmune chronic disease. Classically identified Tregs were at levels equivalent to non-autoimmune controls but the Th40/Treg ratio still predicted autoimmunity. The cohort displayed a wide range of HLA haplotypes including the GWAS identified predictive HLA-DRB1*1501 (DR2). However half the subjects did not carry DR2 and regardless of HLA haplotype, Th40 cells were expanded during disease. In RRMS Th40 cells demonstrated a limited TCR clonality. Mechanistically, Th40 cells demonstrated a wide array of response to CNS associated self-antigens that was dependent upon HLA haplotype. Th40 cells were predominantly memory phenotype producing IL-17 and IFNγ with a significant portion producing both inflammatory cytokines simultaneously suggesting an intermediary between Th1 and Th17 phenotypes.